Asymmetric Impact of Oil Price on Inflation: Evidence from Nepal - Karki, Dipesh; Risal, Hari Gopal (NRB Economic Review, 2019)
This paper investigates asymmetric oil price pass through on inflation in Nepal using time series data of 331 months from April 1987 to February 2018. The paper applies Nonlinear Autoregressive Distributed Lag (NARDL) model to estimate long run and short run asymmetric adjustment of refined petroleum products on Consumer Price Index (CPI). Finding shows presence of long run asymmetric adjustment between price of all petroleum products and CPI. However, when the model is controlled for monetary impact and price level of India, only the price of diesel is found to have long run asymmetric pass through into inflation. The long run cointegrating equation shows unit rise in price of diesel is accompanied by small contraction in CPI in long run by -0.048 units. Meanwhile unit fall in price of diesel is shown to have positive long run pass through in CPI by 0.431 units. This apparent anomaly could be attributed to fact that with rise in price of diesel, demand for cheaper adulterant like kerosene increases thus resulting in fall in CPI Similarly, fall in unit price of diesel could have overall increased industrial demand and other resources which in turn led to significant increase in CPI. Meanwhile, study didn’t find any significant asymmetry in short run between CPI and petroleum products. However, in short run a significant impact on the CPI by actual size of increased price of Petrol and Diesel has been found. Hence, in short run, it shows that it is the size of price increase in Petrol and Diesel; not the price itself that has significant effect on the CPI. Since petroleum products in Nepal are not priced by market, these findings can provide guidelines for future oil pricing in reducing the spillover impact on general price level.